Influencing Factors of Postgraduates' Perceived Usefulness and Continuance Intention Towards Chinese University MOOCs: A Case Study of Chongqing University - Zhang, Qian (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study delves into the factors affecting postgraduates’ perceived usefulness (PU) and continuance intention (CI) to use Chinese University MOOCs, focusing on postgraduates from two engineering majors at Chongqing University, China. Rooted in Expectation - Confirmation Theory (ECM), S-O-R model and Technology Acceptance Model (TAM), the research examines seven variables: Perceived Ease of Use (PEU), Learning Engagement (LEN), Perceived Usefulness (PU), Satisfaction (SAT), Cognitive Presence (CP), Continuance Intention (CI) and Teaching Presence (TP). A quantitative approach was adopted, with 500 valid questionnaires collected. CFA (Confirmatory Factor Analysis) results demonstrated that the measurement model boasted high reliability and validity (AVE > 0.5, Cronbach’s Alpha > 0.7). SEM (Structural Equation Modeling) analysis supported all six hypotheses, revealing significant positive relationships. The findings highlight that both system-related factors (PEU, PU) and interaction-related factors (TP, CP, LEN, SAT) are critical to sustaining postgraduates’ MOOC usage.